A Hidden Diversity in the Atlantic and the SE Pacific: Hamatipedidae n. fam. (Crustacea: Tanaidacea) - Gellert, Marta; Bird, Graham; Stȩpień, Anna; Studzian, Maciej; Błażewicz, Magdalena (Frontiers in Marine Science, 2022)
A new family of paratanaoidean Tanaidacea, the hamatipedids, formerly part of the Typhlotanaidae, is established to accommodate three genera (Hamatipeda and two new). Deep-sea hamatipedids collected from four sites in the Atlantic (Argentine and Guiana basins) and 14 sites from the Southeast coast of Australia were studied using a taxonomic approach combining morphological and morphometric data. Four new species of Hamatipeda and one of a new genus are described from different deep-sea areas of the Atlantic and Pacific oceans. Hamatipeda sima originally classified within Hamatipeda, is transferred to a new genus. We observed that several morphometric characters (i.e., length of the last two pereonites) in different life-stages of one of the new Hamatipeda species (neuter, manca-2, and manca-3) are correlated with the total body length (TBL). Applying a morphometric approach, we aimed: (1) to identify those ontogenetic-dependent characters, and (2) to detect the characters, which can be used in discrimination of Hamatipedidae species, regardless their life-stage.